Aclimatação e adubação de mudas micropropagadas do abacaxizeiro Gold no sul do Estado do Espírito Santo - Bregonci, Izaias dos Santos (2007)
This work was carried at the Centro de Ciências Agrárias da Universidade Federal do Espírito Santo, located in Alegre city, Brasil. The objective was to evaluate the growth of the of the Pineapple plantlets micropropagated [Ananas comosus (L.) Merrill c